Elevated COUP-TFII expression in dopaminergic neurons accelerates the progression of Parkinson’s disease through mitochondrial dysfunction - Kao, Chung-Yang (PLoS Genet, 2020)
Parkinson’s disease (PD) is a neurodegenerative disorder featuring progressive loss of midbrain dopaminergic (DA) neurons that leads to motor symptoms. The etiology and pathogenesis of PD are not clear. We found that expression of COUP-TFII, an orphan nuclear receptor, in DA neurons is upregulated in PD patients through the analysis of public datasets. We show here that through epigenetic regulation, COUP-TFII contributes to oxidative stress, suggesting that COUP-TFII may play a role in PD pathogenesis. Elevated COUP-TFII expression specifically in DA neurons evokes DA neuronal loss in mice and accelerates the progression of phenotypes in a PD mouse model, MitoPark. Compared to control mice, those with elevated COUP-TFII expression displayed reduced cristae in mitochondria and enhanced cellular electron-dense vacuoles in the substantia nigra pars compacta. Mechanistically, we found that overexpression of COUP-TFII disturbs mitochondrial pathways, resulting in mitochondrial dysfunction. In particular, there is repressed expression of genes encoding cytosolic aldehyde dehydrogenases, which could enhance oxidative stress and interfere with mitochondrial function via 3,4-dihydroxyphenylacetaldehyde (DOPAL) buildup in DA neurons. Importantly, under-expression of COUP-TFII in DA neurons slowed the deterioration in motor functions of MitoPark mice. Taken together, our results suggest that COUP-TFII may be an important contributor to PD development and a potential therapeutic target.